Do the cultural and behavioral factors have an impact on adoption of international accounting standards? - Riahi, Olfa; Khoufi, Walid (International Journal of Accounting and Economics Studies, 2017)
In this paper, we try to explain the effect of cultural and behavioral factors on the decision to adopt IFRS in developing countries until 2013. By using contingency theory and based on a sample of 77 developing countries, this head study allowed us to show that the behavioral factors, essentially accounting conservatism, are more dominant that cultural factors behind the decision to adopt IFRS by developing countries (DC).